Early Callous-Unemotional Behavior, Theory-of-mind, and a Fearful/Inhibited Temperament Predict Externalizing Problems in Middle and Late Childhood - Song, Ju-Hyun (J Abnorm Child Psychol, 2016)
Childhood externalizing problems are more likely to be severe and persistent when combined with high levels of callous-unemotional (CU) behavior. A handful of recent studies have shown that CU behavior can also be reliably measured in the early preschool years, which may help to identify young children who are less likely to desist from early externalizing behaviors. The current study extends previous literature by examining the role of CU behavior in very early childhood in the prediction of externalizing problems in both middle and late childhood, and tests whether other relevant child characteristics, including Theory-of-Mind (ToM) and fearful/inhibited temperament moderate these pathways. Multi-method data, including parent reports of child CU behavior and fearful/inhibited temperament, observations of ToM, and teacher-reported externalizing problems were drawn from a prospective, longitudinal study of children assessed at ages 3, 6, and 10 (N=241; 48% female). Results demonstrated that high levels of CU behavior predicted externalizing problems at ages 6 and 10 over and above the effect of earlier externalizing problems at age 3, but that these main effects were qualified by two interactions. High CU behavior was related to higher levels of externalizing problems specifically for children with low ToM and a low fearful/inhibited temperament. The results show that a multitude of child characteristics likely interact across development to increase or buffer risk for child externalizing problems. These findings can inform the development of targeted early prevention and intervention for children with high CU behavior.